"Carne Fraca": Crisis in Brazilian beef processing and the effect of the media on consumers' purchase behaviour. Issue 2 (17th December 2019) - Quevedo-Silva, Filipe; Freire, Otavio; Spanhol-Finocchio, Caroline Pauletto
Abstract : Purpose: Over the last few years, several events have reduced the consumer confidence in relation to food safety. Recently, one event that triggered discussions and concern among consumers in Brazil was the "Carne Fraca" operation which cast doubt on the quality and safety of Brazilian beef. The purpose of this paper is to analyse the impact of the news regarding a national crisis in beef production on consumers' assessment and purchase intention of beef. Design/methodology/approach: A quantitative study was conducted involving 417 respondents in Brazil. The procedure for the analysis consisted of the investigation of two models, incorporating mediation and moderation effects. Findings: The results show that news on the crisis had a positive impact on risk perception. This impact was negatively moderated by consumer scepticism. Risk perception had a negative effect on the assessment of beef and purchase intention. These effects were negatively affected by risk attitude. The news directly affected consumers' assessment of beef and indirectly affected purchase intention through mediation of perceived risk. Originality/value: This study proposes two models, analysing the effect of the media on consumers' assessment of beef and purchase intention, mediated by risk perception. Furthermore, the models analyse the moderating effects of scepticism and consumers' risk attitude.